Handbook of systems biology : concepts and insights - Walhout, A. J. Marian, 1969-; Vidal, Marc, 1962-; Dekker, Job.; ScienceDirect eBooks (Amsterdam ; Boston : Elsever/Academic Press, 2012)
This book provides an entry point into Systems Biology for researchers in genetics, molecular biology, cell biology, microbiology and biomedical science to understand the key concepts to expanding their work. Chapters organized around broader themes of Organelles and Organisms, Systems Properties of Biological Processes, Cellular Networks, and Systems Biology and Disease discuss the development of concepts, the current applications, and the future prospects. Emphasis is placed on concepts and insights into the multi-disciplinary nature of the field as well as the importance of systems biology in human biological research. Technology, being an extremely important aspect of scientific progress overall, and in the creation of new fields in particular, is discussed in 'boxes' within each chapter to relate to appropriate topics. Emphasizes the interdisciplinary nature of systems biology with contributions from leaders in a variety of disciplinesIncludes the latest research developments in human and animal models to assist with translational research. Presents biological and computational aspects of the science side-by-side to facilitate collaboration between computational and biological researchers.
Machine generated contents note: Section I Components of Biological Systems -- 1. Proteomic Analysis of Cellular Systems / Matthias Mann -- 2. The Coding and the Non-coding Transcriptome / Roderic Guigo -- Section II Network Properties of Biological Systems -- 3. Interactome Networks / Marc Vidal -- 4. Gene Regulatory Networks / A.J. Marian Walhout -- 5. Analyzing the Structure, Function and Information Flow in Signaling Networks using Quantitative Cellular Signatures / Norbert Perrimon -- 6. Genetic Networks / Charles Boone -- 7. The Spatial Architecture of Chromosomes / Bas van Steensel -- 8. Chemogenomic Profiling: Understanding the Cellular Response to Drug / Guri Giaever -- 9. Graph Theory Properties of Cellular Networks / Albert-Laszlo Barabasi -- Section III Dynamic and Logical Properties of Biological Systems -- 10. Boolean Models of Cellular Signaling Networks / Reka Albert -- 11. Transcriptional Network Logic: The Systems Biology of Development / Eric H. Davidson -- 12. Reconstruction of Genome-Scale Metabolic Networks / Nathan E. Lewis -- 13. Genotype Networks and Evolutionary Innovations in Biological Systems / Andreas Wagner -- 14. Irreversible Transitions, Bistability and Checkpoint Controls in the Eukaryotic Cell Cycle: A Systems-Level Understanding / Bela Novak -- 15. Phenotypes and Design Principles in System Design Space / Michael A. Savageau -- 16. System Biology of Cell Signaling / Ravi Iyengar -- 17. Spatial Organization of Subcellular Systems / Philippe I.H. Bastiaens -- Section IV Systems and Biology -- 18. Yeast Systems Biology: Towards a Systems Understanding of Regulation of Eukaryotic Networks in Complex Diseases and Biotechnology / Stephen G. Oliver -- 19. Systems Biology of Caenorhabditis elegans / Ben Lehner -- 20. Arabidopsis as a Model for Systems Biology / Ben Scheres -- 21. The Role of the Circadian System in Homeostasis / John B. Hogenesch -- 22. Biological and Quantitative Models for Stem Cell Self-Renewal and Differentiation / Ihor Lemischka -- Section V Multi-Scale Biological Systems, Health and Ecology -- 23. Systems Medicine and the Emergence of Proactive P4 Medicine: Predictive, Preventive, Personalized and Participatory / Nathan D. Price -- 24. Cancer Systems Biology: A Robustness-Based Approach / Hiroaki Kitano -- 25. Systems Immunology: From Cells and Molecules to a Dynamic Multi-Scale System / Shai S. Shen-Orr -- 26. Causal Inference and the Construction of Predictive Network Models in Biology / Eric E. Schadt -- 27. Social Networks, Contagion Processes and the Spreading of Infectious Diseases / Alessandro Vespignani.
Includes bibliographical references and index.
Publisher supplied information; title not viewed.
Elsevier
Keywords: Systems biology -- Handbooks, manuals, etc; Systems Biology; Systems biology; Electronic books